Examining The Moderating Role Of Performance Measurement System On Relationship Between Audit Results And Performance Of Indonesian Local Authorities - Amyulianthy, Rafrini; Muda, Ruhaini; Said, Jamaliah; Setyaningrum, Dyah (The journal of contemporary issues in business and government, 2021)
The objective of this study is twofold. First is examining the effect of audit results on the local government performance. Secondly is examining the moderating role of performance measurement system on the relationship between audit results and local government performance. This study collected 846 local governments’ data from 282 local authorities in Indonesia from 2014 to 2016. The data that employed for audit results were extracted from findings and rectification of audit reports. For the Performance Measurement System, the data were taken from the Government Agency Performance Accountability Report which described the performances of government agencies on the activities and programs implementation which funded by the government. Meanwhile, the local government performances were measured using the total obtained revenue. This study uses multiple regression analysis to explain relationship between the audit results and performance measurement system on local government performance. As the results, it has a positive significant effect on both variables tested. This research also found a significant interaction effect between audit results and performance measurement system on local government. These results assert that local governments with strong Perfomance Measurement System are more effective in responding to negative findings of audit in order to improve their performances in the following years.